THE IMPACT OF LAND USE CHANGE ON COMMUNITY ECONOMY IN WAMBES VILLAGE, MANNEM DISTRICT, KEEROM REGENCY, PAPUA - Yulfigo Naluwi Wandik; Ramandei, Lazarus; Marsal Arung Lamba (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the impact of land use change on the community economy in Wambes Village, Mannem District, Keerom Regency, Papua. The conversion of oil palm plantation land covering 846 hectares into corn farming areas under the government’s Food Estate program has caused significant changes in farmer income structures, livelihood patterns, and community socio-economic dynamics. The study employed a mixed method approach, combining quantitative and qualitative data collection through observation, interviews, questionnaires, and documentation studies. Findings reveal a dual impact: while the Food Estate program initially opened new economic opportunities, the net income of corn farmers (IDR 978,000/quarter) is drastically lower than the previous palm oil income (IDR 13,211,000/month). The decline in productive land from 500 ha to only 2 ha of active corn cultivation reflects the failure of program continuity. The study recommends sustainable land management policies that integrate community participation, subsidy continuity, technical assistance, and protection of customary land rights of indigenous Papuan communities.